The Influence of Brand Image and Brand Performance on the Brand Loyalty Uniqlo - Damar Adi Yudhistira; Muchsin Saggaf Shihab (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The objective of this research is to look into the impact of brand image and brand performance on UNIQLO brand loyalty, as well as the interaction between brand success and brand image on the development of UNIQLO brand loyalty. This research is included in the poll research category and uses questionnaires to be the research instruments. The consumers of the UNIQLO brand become the research sample group that covers 100 respondents. With the help of IBM SPSS Statistics 26.0 software, multiple linear regression analysis is the research method used. The findings of this study indicate a favorable and significant correlation between UNIQLO brand loyalty formation and brand performance and between UNIQLO brand loyalty formation and brand image combination and brand performance. If a brand’s brand image and brand performance are strong, it will affect brand loyalty, which will support the business stability of the brand.